A New Diagnostic System for Detection of 'Candidatus Liberibacter asiaticus' Infection in Citrus - Lu, Lianming (Plant disease, 2013)
In this study, two polyclonal antibodies were produced against the Omp protein of 'Candidatus Liberibacter asiaticus'. First, omp genes were sequenced to exhibit 99.9% identity among 137 isolates collected from different geographical origins. Then, two peptides containing the hydrophobic polypeptide-transport-associated (POTRA) domain and β-barrel domain, respectively, were identified on Omp protein. After that, these two peptides were overexpressed in Escherichia coli and purified by affinity chromatography to immunize the white rabbits. Finally, the antiserum was purified by affinity chromatography. The two Omp antibodies gave positive results (0.454 to 0.633, 1:1,600 dilution) in enzyme-linked immunosorbent assay against 'Ca. L. asiaticus'-infected samples collected from different geographical origins but revealed negative results against other pathogen-infected, nutrient-deficient and healthy samples. The antibody against the POTRA domain of Omp protein could detect 'Ca. L. asiaticus' in 45.7% of the symptomatic samples compared with a 56.2% detection rate with a polymerase chain reaction assay. These new antibodies will provide a very useful supplement to the current approaches to 'Ca. L. asiaticus' detection and also provide powerful research tools for tracking distribution of this pathogen in vivo